The Therapeutic Potential of Plant Polysaccharides in Metabolic Diseases - Xiao-Fang Wang; Xue Chen; Yong Tang; Jian-Ming Wu; Da-Lian Qin; Lu Yu; Chong-Lin Yu; Xiao-Gang Zhou; An-Guo Wu (MDPI AG, 2022)
Plant polysaccharides (PPS) composed of more than 10 monosaccharides show high safety and various pharmacological activities, including immunoregulatory, antitumor, antioxidative, antiaging, and other effects. In recent years, emerging evidence has indicated that many PPS are beneficial for metabolic diseases, such as cardiovascular disease (CVD), diabetes, obesity, and neurological diseases, which are usually caused by the metabolic disorder of fat, sugar, and protein. In this review, we introduce the common characteristics and functional activity of many representative PPS, emphasize the common risks and molecular mechanism of metabolic diseases, and discuss the pharmacological activity and mechanism of action of representative PPS obtained from plants including Aloe vera, Angelica sinensis, pumpkin, Lycium barbarum, Ginseng, Schisandra chinensis, Dioscorea pposite, Poria cocos, and tea in metabolic diseases. Finally, this review will provide directions and a reference for future research and for the development of PPS into potential drugs for the treatment of metabolic diseases.